PERANCANGAN LABORATORIUM PADA CAMPURAN HOT ROLLED SHEET-BASE (HRS-BASE)DENGAN MENGGUNAKAN ASPAL PEN 60/70 DAN ZEOLIT ALAM SEBAGAI FILLER - , Wukirsari Iskandar A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Asphalt and filler has an important role in the mix pliable, but the type of asphalt and filler used has not been able to overcome the problem of premature damage to existing pavement. This study uses asphalt Pen.60 / 70 and natural zeolite as filler on mix-Base Hot Rolled Sheet (HRS-Base) in order to determine whether the natural zeolite can be used as a filler, Marshall characteristics and indirect tensile strength values. Merging the two materials in the testing done with the design of the test specimen using 5 filler content variation, the variation 1 (100% stone dust: 0% natural zeolite), variation 2 (75% stone dust: 25% natural zeolite), variation 3 (50% stone dust: 50% natural zeolite), variations 4 (25% stone dust: 75% natural zeolite) and variation 5 (0% stone dust: 100% natural zeolite). Having obtained the optimum bitumen content of each variation then testing Marshall with soaking time of 0.5 hours and 24 hours, then the Indirect Tensile Strength testing. The results were obtained for the optimum bitumen content variation 1 is 7,1%